Making the Business Case for Sustainability: How to Account for Intangible Benefits—A Case Study Approach. Issue 1 (December 2016) - Kreiss, Cory; Nasr, Nabil; Kashmanian, Richard
Abstract : Sustainability is continuing to change the way businesses operate. Stakeholders are insisting that corporations implement more responsible business practices, and they are holding them increasingly accountable for their associated environmental and social impacts. Research has provided significant contributions toward sustainability‐related tools and best practices, allowing sustainability to be integrated even farther across business operations. However, challenges still exist, preventing many companies from fully integrating sustainability. Although intangible benefits are not commonly included in business case assessments, such benefits can be derived through sustainability initiatives and may offer additional value in evaluating the business case for sustainability. In this article, we review current literature on accounting methods for the business case for sustainability as well as currently available methods or tools that are capable of estimating intangible benefits. In addition, we use case studies to illustrate if, and how, companies are accounting for intangible benefits, and we identify best methods for accounting for intangible benefits.